2006
DOI: 10.1021/jm051252j
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects of N-(1,3-Diphenyl-1H-pyrazol-5-yl)benzamides on Positive Allosteric Modulation of the Metabotropic Glutamate-5 Receptor in Rat Cortical Astrocytes

Abstract: CDPPB [3-cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide] was recently described as the first centrally active, positive allosteric modulator of rat and human metabotropic glutamate receptor (mGluR) mGluR5 subtype. We explored the structural requirements for potentiation of glutamate-induced calcium release in naturally expressed mGluR5 in cultured rat astrocytes and increasing affinity for the allosteric antagonist binding site by evaluating 50 analogues of CDPPB. In the fluorometric calcium assay, CDPPB exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 36 publications
4
65
0
Order By: Relevance
“…A significant drawback of available mGluR5 PAMs is a lack of physiochemical and PK properties suitable for optimal in vivo dosing. Extensive medicinal chemistry efforts based on the CDPPB, ADX-47273, and CPPHA scaffolds de Paulis et al, 2006;Zhao et al, 2007;Engers et al, 2009) have failed to produce compounds with the aqueous solubility and PK profiles required for optimal in vivo studies. Although limited in vivo studies have been performed with these earlier compounds, they have required dosing in DMSO, which can compromise the interpretation of in vivo data.…”
Section: Discussionmentioning
confidence: 99%
“…A significant drawback of available mGluR5 PAMs is a lack of physiochemical and PK properties suitable for optimal in vivo dosing. Extensive medicinal chemistry efforts based on the CDPPB, ADX-47273, and CPPHA scaffolds de Paulis et al, 2006;Zhao et al, 2007;Engers et al, 2009) have failed to produce compounds with the aqueous solubility and PK profiles required for optimal in vivo studies. Although limited in vivo studies have been performed with these earlier compounds, they have required dosing in DMSO, which can compromise the interpretation of in vivo data.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ADX47273 (de Paulis et al, 2006) was identified as a novel selective mGlu5 PAM at the 5th International Metabotropic Glutamate Receptors Meeting . Up to 60 M ADX47273 showed no agonist, antagonist, or allosteric modulator activity at other rat and/or human family III GPCRs (mGlu1-8 and GABA-B).…”
mentioning
confidence: 99%
“…(Kinney et al, 2005;Lindsley et al, 2004), respectively. Subsequent structure-activity relationship study on CDPPB identified several nanomolar potent pyrazole ligands (De Paulis et al, 2006). Although these compounds are potent with an EC 50 value of less than 20 nM, their poor binding affinity (K i ) and high lipophilicity The discoveries of noncompetitive allosteric modulators with high binding affinity and subtype-selectivity entitle the exploration of the physiological functions of mGluR5 in normal and pathological states.…”
Section: Allosteric Modulators and Radiotracers For Mglur5mentioning
confidence: 99%
“…To date, more than 15 mGluR5-selective PET ligands labeled with 18 F or 11 C have been reported (Fig. 6) (Ametamey et al, 2006;De Paulis et al, 2006;Hamill et al, 2005;Honer et al, 2007;Krause et al, 2003;Musachio et al, 2003;Patel et al, 2005;Sanchez-Pernaute et al, 2008;Sime´on et al, 2007;Wang et al, 2007a;Zhu et al, 2007). In 2005, Hamill and colleagues from Merck demonstrated the first successful PET imaging of mGluR5 in rhesus monkeys using [ 18 F]F-MTEB (61) Patel et al, 2005).…”
Section: Pet Imaging Studies Of Mglur5 Functionmentioning
confidence: 99%